Complexity of Tax Aspects in Carbon Tax Implementation - Wijaya, Melinda (PT FORMOSA CENDEKIA GLOBAL, 2023)
The focus on carbon tax has been central in efforts to reduce greenhouse gas emissions. The use of carbon tax policies as a vital tool to address climate change has been implemented in many countries, including Indonesia. However, the implementation of carbon taxes involves a series of complex challenges. This research aims to examine the complexity of tax aspects that pose challenges in the process of implementing carbon tax policies in Indonesia and the strategies the Indonesian government can employ to overcome these challenges. The research adopts a qualitative approach, collecting data through literature review. It explores the multidimensionality and complexity of carbon tax aspects, encompassing policy design, socio-economic impacts, and administrative constraints. The research findings indicate the need for an integrated carbon tax policy design, focusing on setting appropriate rates and ensuring fair revenue allocation. Evaluating the social and economic impacts of carbon taxes becomes a crucial part of understanding the extensive consequences that may arise. Involvement from industries and other stakeholders in the policy design process is an essential element in addressing this complexity. The study also emphasizes the necessity for improvements in administrative infrastructure and monitoring systems to ensure that carbon taxes are not only effective but also accountable in significantly reducing carbon emissions